Combined modified atmosphere packaging and low temperature storage for marketability of red-fleshed dragon fruit (The Philippine Journal of Crop Science, 2018)
Dragon fruit gained popularity in the Philippines because of its attractive red peel and green bracts, nutritive value and reputation for profitability. However, it is a short-seasoned crop and highly perishable due to moisture loss, shriveling, decay and bract discoloration that detracts consumer appeal and limit its marketable life. This study was conducted to extend the storage and shelf life of dragon fruit through modified atmosphere packaging (MAP) in combination with storage at low temperature. Excellent quality fruit harvested at 25-30 days after flowering were sleeved in polystyrene fruit cup and individually packed in either 0.002-inch-thick polyethylene or polypropylene plastic bags. Sample fruits were withdrawn every two weeks from storage (5℃ ) and transferred to 20℃ for shelf life evaluation. MAP-stored fruit remained in excellent condition for up to 6 weeks at 5℃ without any shriveling thus fruit were firm, and bracts remained green. Shelf life at 20℃ was 7 days for fruit stored under 4 weeks and only 3 days if MAP storage extended to 6 weeks. Control fruits on the other hand lasted for only 4 weeks at 5℃ with noticeable change in visual quality and the bracts already exhibiting yellowing and tip browning. Total soluble solids and titratable acidity were higher in polyethylene-packed fruit at its limit of marketability at 20℃. The use of polystyrene fruit cups generally aided in maintaining the visual quality of the fruit by protecting the bracts from breaking during handling.